A z = 5.34 galaxy pair in the Hubble deep field - Spinrad, H; Stern, D; Bunker, A; Dey, A; Lanzetta, K; Yahil, A; Pascarelle, S; Fernandez-Soto, A (1998)
We present spectrograms of the faint V-drop (V606 = 28.1, I814 = 25.6) galaxy pair HDF 3-951.1 and HDF 3-951.2 obtained at the Keck II Telescope. In a recent study, Fernández-Soto, Lanzetta, and Yahil derive a photometric redshift of zph = 5.28+0.34-0.41 (2 σ) for these galaxies; our integrated spectrograms show a large and abrupt discontinuity near 7710 ± 5 Å. This break is almost certainly due to the Lyα forest because its amplitude (1 - fshortv/flongv > 0.87, 95% confidence limit) exceeds any discontinuities observed in stellar or galactic rest-frame optical spectra. The resulting absorption break redshift is z = 5.34 ± 0.01. Optical/near-IR photometry from the HDF yields an exceptionally red (V606 - I814) color, consistent with this large break. A more accurate measure of the continuum depression blueward of Lyα utilizing the imaging photometry yields DA = 0.88. The system as a whole is slightly brighter than L*1500 relative to the z ∼ 3 Lyman break population, and the total star formation rate inferred from the UV continuum is ≈22 h-250 M⊙ yr-1 (q0 = 0.5) assuming the absence of dust extinction. The two individual galaxies are quite small (size scales ≲ 1 h-150 kpc). Thus these galaxies superficially resemble the "building blocks" of Pascarelle and coworkers; if they comprise a gravitationally bound system, the pair will likely merge in a timescale ∼100 Myr.